Sustainable Profitability with Assets Management Analysis: A Case Study of PT Tri Ananda Pratama Balikpapan – Indonesia - Ballinda, Ersalina; Lau, Elfreda Aplonia; Suharyono, Ekrin Yohanes (PT Global Digital Sains Tekno, 2023)
The company's operational activities aim to generate profits to survive and be competitive. Efforts to generate maximum profits cannot be separated from the effective use of company assets The objective of this study is to assess asset management at PT. Tri Ananda Pratama Balikpapan from the perspectives of receivables, inventories, fixed assets, total assets, and working capital turnover to sustain sustainable profitability as determined by net profit margin (NPM) from 2017 to 2019. Ratios are used by the analytical tool; the activity ratio, which includes the working capital, fixed asset, inventory, and account receivable turnover ratios, is one type of ratio that is used. In addition, the net profit margin (NPM) ratio is employed to assess the ongoing profitability of the business. The research results demonstrate that total asset turnover, inventory, fixed assets, and accounts receivable can all raise NPM. However, NPM cannot be raised by working capital turnover. Based on the research results, it is implied that companies can optimize their use by detailing and understanding the needs and life cycle of assets. This will help reduce waste and increase operational efficiency.